ANALISA KEKUATAN BENDING KOMPOSIT EPOXY DENGAN PENGUATAN SERAT NILON - Sari, Nasmi Herlina; Sinarep, S. (Dinamika Teknik Mesin: Jurnal Keilmuan dan Terapan Teknik Mesin, 2011)
The development of composite materials in the field of engineering is increasingly being used. This is because of its properties are superior compared to conventional materials, as the ratio between strength and density are quite high, stiff, the manufacturing process is very simple and resistant to corrosion and fatigue loads. The purpose of this study was to determine the effect the addition of nylon fibers with Epoxy Matrix on the increase in bending strength of epoxy composites.  The objected of this study was the composite of nylon fiber, which is cut 12 mm nylon fiber with epoxy resin as a fastening material. Before performing an experiment testing the tensile fibers has done and known to the stress of 461.22 MPa. There are 3 variations of volume fraction In this experiment, those are volume fraction of 40%, 50%  and  60%, with 3 variation each.  Method in the manufacture of specimens with the way the mould press. Tools to test the specimen is bending test machine (servopulser). Specimens using a standard test of ASTM C 393-94. Bending test results showed that the nylon fiber composite with fiber volume fraction 40% stress of 787.16 MPa, modulus of elasticity of 1.06 GPa, volume fraction of 50% the stress of 902.01 MPa, modulus of elasticity of 1.08 GPa, and for 60% volume fraction of the stress of 950.02 MPa, modulus of elasticity of 0.99 GPa.